2021
DOI: 10.3897/phytokeys.176.63378
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Allium section Rhizirideum (Amaryllidaceae) in South Korea and northeastern China: with a new species from Ulleungdo Island

Abstract: Allium section Rhizirideum is reviewed for South Korea and neighboring northeastern China based on critical observation of wild populations and herbarium materials. Species delimitations are re-evaluated on the basis of morphological and somatic chromosome numbers, resulting in the recognition of five species. Allium dumebuchum from Ulleungdo Island, South Korea, is described as a new species. This species is most similar to A. senescens due to its habits, but is clearly distinguished particularly by its rhomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 1,159 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Our phylogenetic results detected a similar topology to previous studies (Friesen et al 2006;Li et al 2010;Choi et al 2012;Sinitsyna et al 2016;Xie et al 2020b;Jang et al 2021). ITS and cpDNA regions strongly support that A. heterophyllum is a member of section Rhizirideum, and sister to the other species of section Rhizirideum (e.g.…”
Section: Phylogenetic Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Our phylogenetic results detected a similar topology to previous studies (Friesen et al 2006;Li et al 2010;Choi et al 2012;Sinitsyna et al 2016;Xie et al 2020b;Jang et al 2021). ITS and cpDNA regions strongly support that A. heterophyllum is a member of section Rhizirideum, and sister to the other species of section Rhizirideum (e.g.…”
Section: Phylogenetic Analysissupporting
confidence: 89%
“…Although A. heterophyllum is morphologically most similar to A. dumebuchum, these two species are not closely related in the phylogenetic trees. According to previous studies, species in the section Rhizirideum are very widely distributed across the world and exhibit complicated relationships (Friesen et al 2006;Choi et al 2012;Sinitsyna et al 2016;Jang et al 2021), and this section is also regarded as a difficult taxon concerning classification and identification. Thus, morphological and phylogenetic analyses should be conducted at the population level in the future, thereby better investigating the species' relationships.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Eduardia) and the genetic bases of adaptative evolution remain poorly understood for the Indian taxa (Pandey et al 2021). Molecular phylogeny study of the wild Allium in different centers of diversity (Nguyen et al 2008;Xie et al 2019;Jang et al 2021) has helped in unlocking many aspects of the taxon relationships. The present study uncovered a new species relationship with its closest allied species and suggested that the selective habitat pressure has played an important role in the adaptation and evolution of Allium in this habitat which will facilitate uncover more taxa in the genus.…”
Section: Key Tomentioning
confidence: 99%
“…has ca. 37 taxa that are included in four sections distributed mainly in Europe-East Asia, in China (Friesen et al 2006;Choi et al 2012;Jang et al 2021) and also in Russia, Mongolia and Kazakstan (Sinitsyna et al 2016;Friesen et al 2020). Allium senescens L. of sect.…”
Section: Introductionmentioning
confidence: 99%